Is F-2-isoprostane a biological marker for the early onset of type 2 diabetes mellitus? - Kaviarasan, Subramanian; Muniandy, Sekaran; Qvist, Rajes; Chinna, Karuthan; Ismail, Ikram Shah (Medknow Publications, 2010)
Aim: This clinical study was undertaken to investigate whether F-2-isoprostane, a prostaglandin F-2-like compound derived from the non-enzymatic peroxidation of arachidonic acid, could serve as a novel biomarker for early detection of type 2 diabetes mellitus (T2DM) or its complications. Materials and Methods: Twenty-five individuals who had impaired glucose tolerance (IGT) or T2DM were compared with controls. Anthropometry, plasma glucose, hemoglobin A1c, lipid profile and F-2-isoprostane levels were measured in these subjects. Results: Clinical characteristics of subjects with IGT showed significant alteration when compared to subjects with T2DM but not with that of controls having normal glucose tolerance. In the case of isoprostane levels, there existed a significant difference between groups but there is no clear correlation with the clinical characteristics of the subjects. Conclusion: Isoprostane may not serve as a marker for early detection of diabetes. However, its value may predict the oxidative status of the subjects and hence the development of the complications associated with diabetes.